STUDY OF GRAZING INFLUENCES ON PASTURES VEGETATION CONDITION - Nasiyev, B.N.; Zhanatalapov, N.Zh.; Bekkaliyev, A.K. (Западно-Казахстанский аграрно-технический университет имени Жангир хана, 2015)
The researches established the expediency of moderated (65-75% browsing) use of pastures, the change of floristic structure and efficiency, deterioration of agrochemical and agro physical indicators on pastures soil cover at the intensive use of pastures.
Keywords: Pastures; monitoring; browsing; floristic structure; soil cover; efficiency